Optimalisasi Program KKN Melalui Inovasi Pojok Baca Berbasis Permainan Tradisional Sebagai Upaya Mengurangi Waktu Layar (Screen Time) Anak Dusun Somokaton - Ulul Azmi Napitu; Luqman Novianto; Ediana Gradia; Oktavia Kurnia Wati; Yohana Fransiska Bahagia; Afrida Mensi; Rusdy Sangadji; Fathorrohim Fathorrohim; Faisal Bahari; Aleksandro Insani Banera Kom; Intan Kusumawati (Gemi: Jurnal Penelitian dan Pengabdian, 2026)
The rapid development of digital technology has led to an increase in children's screen time and a decline in reading interest in the community. This condition also occurs in Somokaton Hamlet, where children tend to spend more time with gadgets than literacy activities and social games. This article aims to describe the implementation and impact of the Community Service Program (KKN) through the innovation of a Traditional Game-Based Reading Corner as an alternative to non-digital education. The method used is a participatory qualitative approach through the stages of observation, planning, provision of facilities, and implementation of literacy activities integrated with traditional games such as congklak, engrang batok, and bakiak. The results of the program, involving 25 children aged 5–13 years, showed a significant behavior shift. Most children who previously spent their leisure time using gadgets shifted to reading activities and traditional games after the program implementation, where the number of children playing gadget games decreased drastically from 20 to only 4 children. Conversely, children voluntarily visited the reading corner routinely 3–4 times a week for at least 20–30 minutes per session. The integration of literacy and traditional games proved to be able to create a fun learning atmosphere while strengthening character values and preserving local culture. Thus, the innovation of the Traditional Game-Based Reading Corner can be an effective strategy in reducing screen time and increasing children's interest in literacy in a sustainable manner.